2016
DOI: 10.3906/vet-1512-55
|View full text |Cite
|
Sign up to set email alerts
|

Egg production, egg quality, and cecal microbial populations of layersfed diets supplemented with fermented phytogenic feed additive

Abstract: 2.1. Preparation of fermented plants G. procumbens and R. glutinosa, which are commonly grown in Korea, were purchased in a local market in Korea. The leaf (G. procumbens) or root (R. glutinosa) was separated, washed, dried at room temperature, and then cut into small pieces (1 × 1 cm). Fermented feed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Our findings were consistent with previous reports, which showed that dietary supplementation with plant fermentation products was able to affect laying performance and egg quality of layers. Diets supplemented with 1 and 2% fermented phytogenic feed additive could improve laying performance, egg weight, albumen height, and Haugh unit of layers (Park et al, 2016). Yoshida et al (2017) evaluated the effect of the fermented spent mushroom substrate as a dietary additive on egg productivity, suggesting that increased egg production might be related to the protection against stress through the fermentation of waste mushroom beds.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were consistent with previous reports, which showed that dietary supplementation with plant fermentation products was able to affect laying performance and egg quality of layers. Diets supplemented with 1 and 2% fermented phytogenic feed additive could improve laying performance, egg weight, albumen height, and Haugh unit of layers (Park et al, 2016). Yoshida et al (2017) evaluated the effect of the fermented spent mushroom substrate as a dietary additive on egg productivity, suggesting that increased egg production might be related to the protection against stress through the fermentation of waste mushroom beds.…”
Section: Discussionmentioning
confidence: 99%
“…Diet supplementation with Allium compounds possess beneficial effects: significantly reduces cholesterol levels in the plasma of laying hens [61][62][63][64], in egg contents [63] and even protects against several diseases, including cancer [65]. Supplementation with different phytobiotics such as black cumin seeds or leaves and extracts from the Lamiaceae family (such as peppermint, sage, rosemary, thyme and oregano) increase egg production and egg weight [64,[66][67][68][69][70]. However, results for egg production in laying hens with their diet supplemented by Allium compounds are contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…Han et al [ 81 ] found that the relative abundance of Lactococcus in the cecum of broilers was positively correlated with body weight. Moreover, supplementation with a phytobiotic in laying hens increased Lactobacillus relative abundance in the cecum and simultaneously improved egg production as well as egg weights [ 68 ]. Most lactic acid bacteria have an intimate relationships with the health of their animal hosts [ 82 ], so these strains have been widely used as probiotics due to their many beneficial properties [ 83 , 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, studies on a comparison of physiological activity before and after the fermentation of plants and applications to livestock (pigs, poultry, daily cows, etc.) as a natural fermented feed additive have been conducted [24,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%